2018
DOI: 10.1002/wcc.531
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming public resistance to carbon taxes

Abstract: Carbon taxes represent a cost‐effective way to steer the economy toward a greener future. In the real world, their application has however been limited. In this paper, we address one of the main obstacles to carbon taxes: public opposition. We identify drivers of and barriers to public support, and, under the form of stylized facts, provide general lessons on the acceptability of carbon taxes. We derive our lessons from a growing literature, as well as from a combination of policy “failures” and “successes.” B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
134
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(193 citation statements)
references
References 91 publications
5
134
0
9
Order By: Relevance
“…In particular, his analysis highlights how voters are biased towards proposal designs that make the tax less efficient, such as having to set a tax rate that is well below estimates of the social cost of carbon. (For this reason, Carattini et al [44] suggested that carbon taxes be phased in over time.) Lucas Jr [45] highlighted how voters have behavioral biases towards less efficient environmental regulations and what this means for carbon taxation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, his analysis highlights how voters are biased towards proposal designs that make the tax less efficient, such as having to set a tax rate that is well below estimates of the social cost of carbon. (For this reason, Carattini et al [44] suggested that carbon taxes be phased in over time.) Lucas Jr [45] highlighted how voters have behavioral biases towards less efficient environmental regulations and what this means for carbon taxation.…”
Section: Discussionmentioning
confidence: 99%
“…The success of carbon taxation depends on a wide list of factors that need to be revised. Carattini et al and Baranzini et al identified barriers to public acceptance of carbon taxes, underlining the importance of proper policy design coupled with communication on the effects of carbon taxes [51,52]. The literature acknowledges a series of unwanted effects of carbon taxes on distribution of income (heavier burden in the lower income groups) and competitiveness (production costs rise).…”
Section: Discussionmentioning
confidence: 99%
“…To address the global issues related to climate change, the United Nations Framework Convention on Climate Change (UNFCCC) established the Paris agreement in 2015 to deal with greenhouse-gas-emissions mitigation, adaptation, and finance (Carattini et al, 2018). The agreement has representatives of 196 member countries as signatories to the agreement.…”
Section: Introductionmentioning
confidence: 99%